Contingent Coalitions in Environmental Policymaking: How Civil Society Organizations Influenced the Chilean Renewable Energy Boom. - Madariaga, Aldo; Allain, Mathilde (Policy Studies Journal, 2020)
This article analyzes the role of social movements and environmental organizations in crafting contingent coalitions to advance renewable energies in Chile. Until recently, Chile presented several conditions predicting the continuation of an arm's‐length energy policy and a deregulated energy market heavily concentrated on environmentally and socially unfriendly sources. However, gradual but transformative policy change in the last decade has made the country a world leader in renewable energy development. Studying two key moments in energy policy reform, we argue that the contingency of the coalitions that social movements and environmental organizations forged was crucial to the advancement of renewable energy policy and the transformation of the energy sector in the country. The paper advances our understanding of policy change in contexts of high path dependency and status quo bias, and builds the concept of "contingent coalitions," unifying similar but scattered and under‐theorized notions that capture the fluid dynamics of coalition formation and policy change in environmental policymaking.